PENGEMBANGAN BAHAN AJAR DARING BERBANTUAN PLATFORM EDMODO PADA MATERI PERBANDINGAN - Nida Alliyah Nurul Jannah; Anwar Muttaqin; Novaliyosi Novaliyosi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This research aims to gain mathematics teaching materials that can be used online with the help of the Edmodo platform for grade VII junior high school students which has the criteria in learning mathematics at the classroom. The method used in this case is research and development (R&D) method with the ADDIE model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The subjects in this research were 32 students of class VII SMP Negeri 3 Kramatwatu, and involved media experts and material experts as well as mathematics teachers as validators. The data collection technique was done by giving a questionnaire. The initial analysis was carried out descriptively, while the feasibility data analysis was carried out as follows. (1) online teaching material products assisted by the Edmodo platform are compiled which will later be in the form of powerpoints and videos, (2) the feasibility of media and materials is based on the validation results of 80.5% media experts and 78.46% material experts so that they are included in the appropriate criteria, while the results teacher's assessment of 79% indicates the criteria are feasible. The revised product will be tested on students through online trials with 82.88% results, which shows very good criteria. Thus, online teaching materials assisted by the Edmodo platform on comparative materials are appropriate to be used as learning materials for mathematics.